Needs Analysis of Students on Listening Course Instruction - Resnita Dewi; Anastasia Baan; Sofyan (Journal of English Education and Teaching, 2023)
The Listening Course is one of the mandatory courses in the Language and Literature Education Study Program in university. This course is crucial as listening is an essential language skill that is frequently used in daily life. This study examines the needs of students in learning listening at Universitas Kristen Indonesia Toraja. The study employs a mixed-method design, using survey and interview techniques on 33 students of the Indonesia Language and Literature Education Study Program in UKI Toraja who take the Listening Course. The results indicate that the students require a more engaging and innovative learning process in order to be interested and comprehend the material of the Listening Course. Therefore, the needs of students in the Listening Course instruction include improvement or revision of the learning material, learning media, learning methods, and relevant teaching materials that are suitable for current students.